2020
DOI: 10.1186/s13613-020-0644-2
|View full text |Cite
|
Sign up to set email alerts
|

Transpulmonary thermodilution detects rapid and reversible increases in lung water induced by positive end-expiratory pressure in acute respiratory distress syndrome

Abstract: Purpose: It has been suggested that, by recruiting lung regions and enlarging the distribution volume of the cold indicator, increasing the positive end-expiratory pressure (PEEP) may lead to an artefactual overestimation of extravascular lung water (EVLW) by transpulmonary thermodilution (TPTD). Methods:In 60 ARDS patients, we measured EVLW (PiCCO2 device) at a PEEP level set to reach a plateau pressure of 30 cmH 2 O (HighPEEP start ) and 15 and 45 min after decreasing PEEP to 5 cmH 2 O (LowPEEP 15′ and LowPE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…In the last decade, a metaanalysis showed that lung ultrasound had a high sensitivity and speci city in critically ill patients who were characterized by pulmonary pathology (20), especially in aspect of assessing EVLW (21,22). The association of EVLW determined by PiCCO 2 with PaO 2 / FiO 2 or OI is affected by BW, height, or PEEP (23)(24)(25)(26). According to previous report, LUS as a convenient, noninvasive and portable technique could detect various pathophysiological changes including lung edema and derecruited lung (9,13,27), and LUS can detect the increased EVLW by the appearance of B-lines in ARDS (28).…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, a metaanalysis showed that lung ultrasound had a high sensitivity and speci city in critically ill patients who were characterized by pulmonary pathology (20), especially in aspect of assessing EVLW (21,22). The association of EVLW determined by PiCCO 2 with PaO 2 / FiO 2 or OI is affected by BW, height, or PEEP (23)(24)(25)(26). According to previous report, LUS as a convenient, noninvasive and portable technique could detect various pathophysiological changes including lung edema and derecruited lung (9,13,27), and LUS can detect the increased EVLW by the appearance of B-lines in ARDS (28).…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, a meta-analysis showed that lung ultrasound had a high sensitivity and specificity in critically ill patients who were characterized by pulmonary pathology [ 20 ], especially in aspect of assessing EVLW [ 21 , 22 ]. The association of EVLW determined by PiCCO 2 with PaO 2 / FiO 2 or OI is affected by BW, height, or PEEP [ 23 26 ]. According to previous report, LUS as a convenient, noninvasive and portable technique could detect various pathophysiological changes including lung edema and derecruited lung [ 9 , 13 , 27 ], and LUS can detect the increased EVLW by the appearance of B-lines in ARDS [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, a meta-analysis showed that lung ultrasound had a high sensitivity and speci city in critically ill patients who were characterized by pulmonary pathology (23), especially in aspect of assessing EVLW (24,25). The association of EVLW determined by PiCCO 2 with PaO 2 / FiO 2 or OI is affected by BW, height, or PEEP (5)(6)(7)(8). According to previous report, LUS as a convenient, noninvasive and portable technique could detect various pathophysiological changes including lung edema and derecruited lung (19,20,26), and LUS can detect the increased EVLW by the appearance of B-lines in ARDS (27).…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring EVLW with pulse indicator continuous cardiac output (PiCCO 2 ) device is available at the bedside for estimating the physiologic correlated to pulmonary edema. However, accumulated evidences demonstrated that an association of EVLW and PaO 2 /FiO 2 or oxygenation index (OI) is affected by body weight (BW), height, or positive end-expiratory pressure (PEEP) (5)(6)(7)(8). Moreover, detection of EVLW by a PiCCO 2 device is invasive and inconvenient.…”
Section: Introductionmentioning
confidence: 99%